MOTIVASI ATLET RENANG KELOMPOK UMUR II (USIA 13-14 TAHUN) DI PERKUMPULAN RENANG MARLIN KOTA BLITAR - FUADIL AZIZAH, SILVIA (Jurnal Prestasi Olahraga, 2013)
The purpose of this study was to determine how significant the motivation of the swimming group II (aged 13-14 years old) in Marlin swimming community Blitar. The research method that was used in this study was descriptive research, since in the research there was no counting. The samples of this study were the athletes, parents and coach. The data collection techniques that were used in this study were observation, interview and documentation. In doing the observation, the researcher observed the athletes directly in order to know everything that could motivate them. There were several data that were intrinsic motivation, extrinsic motivation, and other factors that influenced motivation. The result of study toward the swimming athlete in group II (aged 13-14 years old) shown that the athletes who had high motivation could be seen from their attendance list in every exercise and their achievements in every match. In conclusion, the athlete who got intensive attendance in their exercised and many achievements in their records had high motivation. Keywords : motivation, swimming athletes, group II (13-14 years old)